Anxiety and depression risk in Taiwan women with breast cancer and cervical cancer - Yang, Chiu-Ming; Sung, Fung-Chang; Mou, Chih-Hsin; Liao, Chun-Hui; Wang, Po-Hui; Shieh, Shwn-Huey (Frontiers in Oncology, 2022)
Background: Study comparing mental disorder risks between women with breast cancer and cervical cancer is lack. This study compared risks of developing anxiety and depression between women with breast cancer (BC cohort) and women with cervical cancer (CC cohort) using insurance claims data of Taiwan. Methods: From the 2000-2016 data, we identified a BC cohort and BC controls (N=96,862) and a CC cohort and CC controls (N=26,703), matched by propensity scores. Incident mental disorders and Cox method estimated related cancer cohort to control cohort hazard ratios (HR) and 95% confidence Intervals (CI) were estimated by the end of 2016. Results: Compared to the CC cohort, BC cohort had slightly higher incident anxiety (15.9 versus 15.5 per 1000 person-years) and depression (6.92 vs. 6.28 per 1000 person-years). These mental disorders were higher in respective cancer cohorts than controls. The BC cohort to BC controls adjusted HRs of anxiety and depression were 1.29 (95% CI=1.25-1.33) and 1.78 (95% CI=1.69-1.87), respectively. The corresponding adjusted HRs for the CC cohort were 1.12 (95% CI=1.06-1.18) and 1.29 (95% CI=1.18-1.41). The combined incidence rates of both disorders were 1.4-fold greater in the BC cohort than in BC controls (22.8 vs 15.8 per 1000 person-years), and 1.2-fold greater in the CC cohort than in the CC controls (21.7 vs 18.3 per 1000 person-years). Conclusion: Women with breast cancer or cervical cancer are at an elevated likelihood of developing anxiety and depression disorders. These incident disorders are slightly higher in those with breast cancer.